2018
DOI: 10.1016/j.apcata.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The primary stages of polyoxomolybdate catalyzed cyclohexanone oxidation by hydrogen peroxide as investigated by in situ NMR. Substrate activation and evolution of the working catalyst

Abstract: The primary stages of polyoxomolybdate catalyzed cyclohexanone oxidation by hydrogen peroxide as investigated by in situ NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…This has as for consequence the formation of peroxocomplexes highlighted by several techniques (X-ray diffraction, FTIR, and Raman spectroscopies). These complexes, with an oxidizing power stronger than that of H2O2, have been shown to be very active in several reactions [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]29]. In our case, we could admit that the reduced POM, from the first stage, oxidizes and simultaneously forms peroxocomplexes "peroxo-POMox".…”
Section: Characterization Of the Used Catalystmentioning
confidence: 68%
“…This has as for consequence the formation of peroxocomplexes highlighted by several techniques (X-ray diffraction, FTIR, and Raman spectroscopies). These complexes, with an oxidizing power stronger than that of H2O2, have been shown to be very active in several reactions [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]29]. In our case, we could admit that the reduced POM, from the first stage, oxidizes and simultaneously forms peroxocomplexes "peroxo-POMox".…”
Section: Characterization Of the Used Catalystmentioning
confidence: 68%
“…These peroxo species were reported by several authors as the active species in the formation of oxygenated compounds. They were evidenced by multinuclear NMR spectroscopies in the cases of H 3 [2,21].…”
Section: Introductionmentioning
confidence: 94%
“…In the second step, the addition of hydrogen peroxide led to a POM color change from blue to yellow that is attributed to the POMred oxidation. It was reported that in the presence of hydrogen peroxide, peroxo species such as {PO 4 [2,21]. This step can be explained by the following equation: During the 20 h of reaction, the peroxo-POM species will react with some products from the Eq.…”
Section: Reaction Pathwaymentioning
confidence: 99%
See 2 more Smart Citations